Synthesis and Characterization of Titania-Rice Husk Silica Composites as Photocatalyst - Posman Manurung; Rudy Situmeang; Ediman Ginting; Indra Pardede (Universitas Gadjah Mada, 2015)
This article describes the synthesis of titania-silica composites by a sol-gel method using a mixture of silica of rice husk and titanium butoxide sols. Microstructures were examined at calcination temperature in the range of 500 to 700 °C, with temperatures interval of 50 °C. The sintered catalysts were subsequently tested for photodegradation of methylene blue (MB) under ultraviolet and sunlight rays. Physical characteristics were analyzed using X-ray diffraction (XRD), scanning electron microscopy (SEM)/energy dispersive X-ray spectroscopy (EDS), and Brunauer-Emmett-Teller (BET). The XRD results did not show the presence of silica crystal phase in each sample. The results showed that the highest BET surface area of samples was obtained at the temperature of 650 °C. In sample calcined 500 °C, the activity of the catalyst on MB was relatively similar in both sunlight and ultraviolet rays.